Blasphemy and apostasy in Islam : debates on Shi'a jurisprudence - Kadivar, Mohsen (In translation, modern Muslim thinkers., 2021)
This book tells the story of Rāfiq Taqī, an Azerbaijani journalist and writer, who was condemned to death by an Iranian cleric for a news article in 2006 that was deemed blasphemous. Mohsen Kadivar debates the case with Muhammad Jawad Fazel, the son of Grand Ayatollah Fazel Lankarānī who issued the fatwa pronouncing the death penalty on Taqī.